The last sanctum of archetypes - Gutman Mušič, Maja (Poligrafi, 2023)
Despite numerous attempts to integrate dream research into a vast array of sci-entific disciplines, there appears to be no consensus on why and how we dream. This millennia-old universal human phenomenon appears to be too elusive to be thoroughly understood by a single scientific discipline and too complex and data--rich to be studied only theoretically. However, another dimension to dreams and dreaming could promise an integrative approach: the culture-historical compo-nent that merges with recent advances in artificial Intelligence. This paper briefly examines conceptual understandings of dreams before the dawn of modern science – specifically, the Native american, Mesopotamian, ancient Greek, and Hippocra-tic principles of dream practices and knowledge – in an attempt to understand the contemporary dream research field better and to outline future avenues for a data-driven approach while remaining grounded in its epistemological foundation.
Keywords: ancient dreaming; archetypes; arhetipi; artificial intelligence; cross-cultural dream analysis; dream data; medkulturna analiza sanj; podatki o sanjah; starodavno sanjanje; umetna inteligenca